Labor mobility from R&D-intensive multinational companies: Implications for knowledge and technology - Jacob Rubæk Holm; Bram Timmermans; Christian R. Østergaard; Alexander Coad; Nicola Grassano; Antonio Vezzani (European Commission, Joint Research Centre (JRC), 2019)
Private sector R&D is largely concentrated in a few multinational companies (MNCs), which thus play an important role in the creation of knowledge and technology in the economy. The mobility of labor between these firms and the rest of the economy is therefore an important mechanism for the diffusion of knowledge. This paper analyses in great detail the flow of labor between firms with specific emphasis on flows to and from R&D intensive MNCs. Using linked employer-employee data for Denmark, we match employees moving from R&D intensive MNCs to other employees switching jobs. We find that employees are more inclined to move between R&D intensive MNCs and their subsidiaries rather than between these firms and other firms in the economy. This is particularly true for high skill employees. Our results suggest that other domestic firms are to a larger extent kept out of the 'knowledge spillover' loop, which provide them with fewer opportunities to learn from the R&D intensive MNCs. In other words, R&D intensive MNCs and their subsidiaries form a kind of sub labor market within the national labor market; employees exhibit higher mobility within this group of firms than between this group and the rest of the labor market.
Keywords: J21; F23; O32; 330; Labor mobility; Multinational companies; Knowledge flows; R&D